The Neurocognitive Study for the Aging: Longitudinal Analysis on the Contribution of Sex, Age, Education and APOE ɛ4 on Cognitive Performance - Chadjikyprianou, Andreas; Hadjivassiliou, Marilena; Papacostas, Savvas; Constantinidou, Fofi (Frontiers in Genetics, 2021)
Objective: The effects of normal cognitive aging on executive functions (EF), Verbal Episodic Memory (VEM) across a five-year period and the contribution of age, sex, education, and APOe4 in a group of older old Greek Cypriots across a five-year period were investigated. Design: NEUROAGE, the premier project on cognitive aging in Cyprus is a prospective longitudinal study with a rolling admission process. Participants are assessed at baseline and retested every 24-30 months. Subjects: 170 participants, 86 men and 84 women with ages ranging between 60 and 88 years (mean = 73.21, SD=5.84). Education, 2-20 years (mean = 9.07, SD=4.27) Results: A Repeated Measures Multivariate Analysis of Covariance (MANCOVA) was conducted with one between-subject factor: sex; two covariates: age and education, while Time (time 1, time 2, time 3) served as a within – subject factor. Time did not have an effect on MMSE, EF or VEM. Also, sex had no effect on MMSE, EF and VEM. There was no time by sex interaction. Age and Education significantly predicted the EF performance, p < 0.05; p < 0.001 and VEM performance, p < 0.001; p < 0.001. Furthermore, there was a significant interaction effect between time and education, for EF, p < 0.001. Performance of the APOE e-4 carriers did not differ on any of the above measures as compared to performance of non-carriers in this cognitively healthy older adult group. Conclusions: Cognitively healthy adults maintained overall cognitive performance across the five-year period. Male and female participants performed similarly and the pattern of change over time was similar across the two sexes. Education was predictive of VEM and EF performance across time, resulting in different patterns of change across time. Specifically, while the overall performance on EF tasks did not change significantly across time, the rate of change was related to the years of education. This was not the case for the VEM and MMSE. APOE results did not differentiate participants' performance. Implications of findings are discussed.